Approaches towards individualized immune intervention - Giese, Thomas; Sommerer, Claudia; Zeier, Martin; Meuer, Stefan (Digestive diseases, 2010)
Long-term immunosuppression causes a significantly increased risk for the development of malignancies in transplanted patients. A link between immunosuppression and incidence of cancer is well documented and involves the effect of immunosuppression on antitumor surveillance and antiviral adaptive immune responses. Using a recently described pharmacodynamic assay, a strong correlation between the incidence of malignancies and the individual degree of immunosuppression after cyclosporin A treatment in patients with kidney transplants was observed. The availability of a quantitative and quick laboratory test for the assessment of the individual functional activity of immunocompetent cells crucial for transplant rejection, defense against viral infection and tumor surveillance, along with the ability to adjust doses of immunosuppressive agents such that patients are largely protected against malignant disease and/or viral infection while maintaining a stable allograft function, represents an enormous breakthrough in transplantation medicine and advances our attempts to individualize treatment in transplanted patients.
Gesehen am 09.06.2021